Pengaruh Big Five Personality terhadap Kinerja Karyawan Operasional PT Angkasa Pura Indonesia Bandara Syamsudin Noor - Novalia, Nafisyah; Rachmawati, Desiana; Jumlad, Walid (Huma: Jurnal Sosiologi, 2025)
The performance of human resources (HR) plays a crucial role in determining the success of the company, including in the service sector such as airports. This study aims to analyse the influence of the big five personality model dimensions on employee performance in the Operations Department of PT Angkasa Pura Indonesia at Syamsudin Noor National Airport Banjarmasin. The five dimensions of personality analysed include openness to experience, conscientiousness, extraversion, agreeableness, and neuroticism. The research method used a quantitative approach with data collection techniques through a Likert scale-based questionnaire survey. The research sample totalled 48 employees, determined using the Isaac and Michael formula with an error rate of 5%. Data analysis involves classical assumption tests, such as normality test, heteroscedasticity test, and multicollinearity test, as well as hypothesis testing using multiple linear regression, partial test (T test), and coefficient of determination test. The results showed that the dimensions of openness to experience (t = 2.056, p = 0.046), conscientiousness (t = 2.899, p = 0.006), and agreeableness (t = 2.218, p = 0.032) had a significant effect on employee performance. In contrast, the dimensions of extraversion (t = -0.333, p = 0.741) and neuroticism (t = 1.029, p = 0.309) have no significant effect on employee performance. The coefficient of determination analysis showed that the regression model used was able to explain 70.6% of the variation in employee performance (R² = 0.706). The findings confirm the importance of considering personality characteristics, particularly openness to experience, conscientiousness, and agreeableness, in HRM to improve employee performance. This research provides a practical contribution to HRM in the service industry, as well as a reference for management in designing performance improvement strategies based on employee personality characteristics.